FIGURATIVE LANGUAGE ANALYSIS IN RAEF HAGGAG’S SONG - Crismonika, Titania; Efendi, Dedi; Afrilesa, Rini (Krinok:Jurnal Linguistik Budaya, 2024)
In this research the writer analyzed the figurative language in Raef Haggag songslyric on the Mercy album that consist to four song there are Trust, Mercy, All About Me,and More Than Me And You. The purpose of the research to find the kind of figurativelanguage and messages in Raef Haggag’s songs. The method of the research uses qualitative method. To analyzing the data the writer use library research. The first step the writer read the Raef Haggag Song’s lyrics several times and understanding the text lyric. The second find out the important data and selected the data that can analysis. The last step write down or making a note about the data. The result of this research thewriter found six kinds of figurative language thereare: Hyperbole, Metaphor, Symbol, Personification, Paradox, and Simile. The datum thatthe writer found from four song lyrics are twenty. In this research the writer also found the messages in the songs lyric by Raef Haggag like struggle, never give up, patients andthankfully.